The Mediating Role of Perceived Organizational Support in the Effects of Job Stress on Occupational Commitment: Research on Nurses Working in a Foundation University Hospital - KOÇOĞLU SAZKAYA, MERVE (BEZMIALEM VAKIF UNIV, 2021)
Objective: This study aimed to reveal the relationship between the concepts of job stress, perceived organizational support, and occupational commitment on nurses, who are one of the occupational groups most affected by the coronavirus 2019. Only a few academic studies on the relationships between these concepts were carried out in the literature. Therefore, this study aimed to fill the gap mentioned in the literature. Methods: This study is a quantitative research conducted on 270 nurses working in a foundation university hospital in Istanbul. the data in this study were collected using the questionnaire method, and statistical analyses were performed using SPSS. The participants' demographic characteristics, factor and reliability analyses of job stress, perceived organizational support and occupational commitment variables, mean values of variables, and regression analysis to determine the effects of variables were conducted within the scope of the research. Results: According to the research results, there are significant relationships between job stress, perceived organizational support, and occupational commitment. Perceived organizational support plays a full-mediating role on the effects of job stress, and occupational commitment is another result of the study. Conclusion: In this study, the relationships between the concepts of job stress, perceived organizational support, and occupational commitment are determined. According to the research results, although nurses are exposed to job stress due to working conditions, their occupational commitment increases with the support they receive from their organizations.
Keywords: Job stress; perceived organizational support; occupational commitment; COVID-19; PERFORMANCE; TEACHERS; EFFICACY